Treatment of root perforation by intentional reimplantation: a case report - Poi, Wilson Roberto [UNESP]; Sonoda, Celso Koogi [UNESP]; Salineiro, S. L.; Martin, S. C. (Munksgaard Int Publ Ltd, 1999)
Intentional reimplantation is defined as a procedure in which an intentional tooth extraction is performed followed by reinsertion of the extracted tooth into its own alveolus. Int his paper, intentional reimplantation is described and discussed as a treatment approach to root canal instrument separation in conjunction with root perforation. An 8-year follow-up case report is presented. The reimplanted tooth is now a fixed bridge abutment. Although successful in this case, the intentional reimplantation procedure should be considered a treatment of last resort, that is, when another treatment option is not viable for the treatment of root perforation/instrument retrieval.
Keywords: dental reimplantation; intentional reimplantation; root canal treatment